The Impact of Pitch and Timbre Cues on Auditory Grouping and Stream Segregation - Oh, Yonghee; Zuwala, Jillian C.; Salvagno, Caitlin M.; Tilbrook, Grace A. (Frontiers in Neuroscience, 2022)
In multi-talker listening environments, the culmination of different voice streams may lead to the distortion of each source’s individual message, causing deficits in comprehension. Voice characteristics, such as pitch and timbre, are major dimensions of auditory perception and play a vital role in grouping and segregating incoming sounds based on their acoustic properties. The current study investigated how pitch and timbre cues (determined by fundamental frequency, notated as F0, and spectral slope, respectively) can affect perceptual integration and segregation of complex-tone sequences within an auditory streaming paradigm. Twenty normal-hearing listeners participated in a traditional auditory streaming experiment using two alternating sequences of harmonic tone complexes A and B with manipulating F0 and spectral slope. Grouping ranges, the F0/spectral slope ranges over which auditory grouping occurs, were measured with various F0/spectral slope differences between tones A and B. Results demonstrated that the grouping ranges were maximized in the absence of the F0/spectral slope differences between tones A and B and decreased by 2 times as their differences increased to ± 1-semitone F0 and ± 1-dB/octave spectral slope. In other words, increased differences in either F0 or spectral slope allowed listeners to more easily distinguish between harmonic stimuli, and thus group them together less. These findings suggest that pitch/timbre difference cues play an important role in how we perceive harmonic sounds in an auditory stream, representing our ability to group or segregate human voices in a multi-talker listening environment.